The Influence of Service Quality and Marketing Communication on Prospective Students' Decisions Moderated by The Marketing Mix - Lisa Teresa; Endyastuti Pravitasari (Return : Study of Management, Economic and Bussines, 2023)
This journal aims to test and analyze the effect of service quality and marketing communication on the decisions of prospective new students and is moderated by the marketing mix. A total of 250 respondents as a sample were prospective students who wanted to continue their education to university. Random data collection  by distributing research questionnaires through social media. Smart PLS software is used in research with the results of service quality having a significant effect on the decisions of prospective students, marketing communications have a significant effect on the decisions of prospective students  , and the marketing mix has a significant effect on the decisions of prospective students. In addition, the marketing mix can significantly moderate the influence of service quality on the decisions of prospective students. The marketing mix has also been shown to have a significant effect on moderating the influence of marketing communications on prospective student decisions. Following up on the findings in this study, the decision of prospective students to choose a university can be optimized through service quality, marketing communication, and marketing mix.